Recent Advances in the Surgical Treatment of Differentiated Thyroid Cancer: A Comprehensive Review - Raghunandan Venkat; Marlon A. Guerrero (The Scientific World Journal)
Differentiated thyroid cancers have become one of the fastest growing malignancies in the world. While surgery has remained the cornerstone of management of these tumors, the surgical approach has seen numerous innovations over the past few decades. The use of video-assistance and robotics has revolutionized thyroid surgery. This paper provides a comprehensive evaluation of the different approaches to thyroid surgery, the utility of prophylactic and therapeutic lymph node dissection, and evidence-based guidelines in the treatment of differentiated thyroid cancers. Minimally invasive video-ssisted thyroidectomy is both safe and effective in the hands of the trained surgeon and, in selected patient populations, has comparative perioperative morbidity and better cosmesis as compared to conventional open thyroidectomy. It is universally accepted that therapeutic central lymph node dissection should be performed when metastatic lymph nodes are identified on physical exam, ultrasound, or intraoperatively. In the absence of overt nodal metastasis, the role of elective prophylactic central lymph node dissection remains a matter of debate and prospective, randomized studies are warranted to evaluate the utility of this procedure.